RISK OF IRON DEFICIENCY ANEMIA AND CERVICAL LESIONS IN INTRAUTERINE DEVICE TYPE Cu T 380 A APPLICATION - Mayun Mayura, I Gusti Putu (E-Journal Obstetric & Gynecology Udayana, 2014)
Abstract Background: Since expansion of population number became global issue, contraception programme had primary role, one contraception methods was IUD Cu T 380 A, that succesfully reduce total fertility rate from 6,4 to 3,2. In application of IUD Cu T 380 were found high rate of discontinuity as 15 percent, bleeding and infection were the main reason of discontinuity. The study objective was to know risk of iron deficiency anemia and cervical lesion on IUD Cu T 380 A application at least one year.Methods: Case-Control analytic study at the Obstetrics and Gynaecology Department of Sanglah Hospital was conducted on Jully 1, 2011 until July 15, 2015. Research samples were obtained from women who were reproductive age  and attended Obstetrics Gynecology Outpatient clinic of Sanglah Hospital, Denpasar. Samples were selected based on the random sampling of the reachable population after fulfilled the inclusion and exclusion criteria. Peripheral blood sampling of haemoglobin and profile iron level conducted by ELISA technique at Prodia laboratory and done gynecology examination at Obstetrics Gynecology Outpatient clinic of Sanglah Hospital to obtained cervical lession. Data was statistically analyzed with Shapiro Wilk test for normality, homogeneity test with the T independent  test and comparative test with the Chi-Square , by using the SPSS 17 for windows® version.Results: The average age, education and economic on both groups were homogeneous. The odds ratio was 4,8 in IUD Cu T 380 A group for iron deficiency anemia, Aplication of Intrauterine device type Cu T 380 A  increase  risk of iron deficiency anemia 4 time (OR = 4,80; CI 95% = 1,04-22,10; p =0,036) than non user. The odds ratio was 7,65 in IUD Cu T 380 A group for cervical lession, Aplication of Intrauterine device type Cu T 380 A  increase  risk of cervical lession 7 time (OR = 7,65; CI95% = 1,37-42,71; p =0,012) than non userConclusion : Risk of iron deficiency anemia are four times greater and cervical lesions are seven times greater after Intraterine device type Cu T 380 A application in one year.   Keywords: Iron deficiency anemia, cervical lesion, type Cu T 380 A IUD